2007
DOI: 10.1530/eje-07-0088
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin detection in fine-needle aspirates of cervical lymph nodes: a technique for the diagnosis of metastatic differentiated thyroid cancer

Abstract: Background: Fine-needle aspiration cytology is frequently used for differential diagnosis of neck masses of unknown origin. Inconclusive and even false-negative results are not uncommon. Aim: To evaluate the utility of thyroglobulin (Tg) measurement in fine-needle aspirates (FNA-Tg) for detecting cervical lymph node (CLNs) metastases from differentiated thyroid carcinomas. Methods: An ultrasound-guided fine-needle aspiration was done in 67 patients with 83 suspicious enlarged CLNs to obtain material for cytolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 26 publications
5
137
1
6
Order By: Relevance
“…Cutoffs used in previous studies have varied widely, without a consensus about the most appropriate level (6,19,20). However, a recent study with 168 patients that analyzed 4 different levels of cutoffs (1, 10, 100 ng/mL and FNAB-Tg mean ± SD) indicated that the best level for diagnosis of DTC persistence/recurrence was < 10 ng/mL (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutoffs used in previous studies have varied widely, without a consensus about the most appropriate level (6,19,20). However, a recent study with 168 patients that analyzed 4 different levels of cutoffs (1, 10, 100 ng/mL and FNAB-Tg mean ± SD) indicated that the best level for diagnosis of DTC persistence/recurrence was < 10 ng/mL (16).…”
Section: Discussionmentioning
confidence: 99%
“…(21) that demonstrated that sTg interferes with FNAB-Tg measurement only when high sTg levels are present. These authors, based on recent studies (19,20), suggest that in all patients who do not have high levels of sTg, a detectable level of FNAB-Tg …”
Section: Discussionmentioning
confidence: 99%
“…We compared sensitivity, specificity, PPV, NPV and diagnostic accuracy of FNA-Tg levels of LN according to the functional sensitivity of Tg (0.7 ng/ml) (3,22) and the value determined by ROC curve (6.0 ng/ml), with those of FNAC (Table 4). In addition, FNA-Tg/sTg ratio was also used as a cut-off value to diminish the influence of sTg in preoperative patients (19,23) (Table 4) FNAC alone showed the lowest sensitivity (88.4%) but the highest specificity (99.6%).…”
Section: Fna-tg and Final Outcomementioning
confidence: 99%
“…Fine needle aspiration cytology (FNAC) is recommended for diagnosis of metastatic LNs in thyroid cancer (3,4). When Positive serum Tg antibody (TgAb) is known to lower serum Tg (sTg) levels, and this may be even more important in DTC patients prior to thyroidectomy and/or radioactive iodine therapy in whom a higher rate of positive TgAb has been reported (17).…”
Section: Introductionmentioning
confidence: 99%
“…These results may occur in cases of small or cystic LN metastases, which reflect a lack of tumor cells detected during the FNAB procedure (11). Nevertheless, the use of Tg-FNAB alone has several limitations, and despite being well established as an important tool in the investigation of suspicious LN metastases, Tg-FNAB presents variable results between metastatic and non-metastatic LNs (3,4,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). This subject has been the topic of recent reviews and meta-analysis studies (12,13).…”
Section: Thyroglobulin and Anti-thyroglobulin Antibodies In Needle Wamentioning
confidence: 99%